The Effect of Booklet-Based Nutrition Education During the First 1,000 Days of Life on Parental Attitudes - Andi Maryam; Andi Elis; Ramlah (Papua Medicine and Health Science, 2025)
The success of adequate nutritional fulfillment during the First 1,000 Days of Life is strongly influenced by parental attitudes in decision-making related to maternal dietary patterns during pregnancy, exclusive breastfeeding, and complementary feeding practices (complementary foods for breastfed infants); however, nutrition practices in accordance with recommended guidelines remain suboptimal, indicating the need for effective educational strategies. This study aimed to analyze the effect of booklet-based nutrition education during the First 1,000 Days of Life on parental attitudes at the Benteng Primary Health Care Center (UPT Puskesmas Benteng). A pre-experimental study design with a one-group pretest–posttest approach was conducted from August to September 2025 among 104 parents with children aged 0–24 months, selected using purposive sampling. Data were collected using an attitude questionnaire administered before and after the booklet-based nutrition education intervention and analyzed using the Wilcoxon Signed Rank Test. The results demonstrated a substantial increase in positive parental attitudes, from 7.7% at pretest to 88.5% at posttest, with a p-value of 0.000 (p < 0.05), indicating a significant effect of booklet-based nutrition education on parental attitudes. These findings confirm that booklet media are effective in enhancing positive parental attitudes toward nutritional fulfillment during the First 1,000 Days of Life and are recommended as an applicable nutrition education medium in primary health care settings.